Using the Affective Domain to Enhance Teaching of the ACGME Competencies in Anesthesiology Training - Yanofsky, Samuel D. (J Educ Perioper Med, 2014)
Teaching and assessing the advanced competencies will continue to be a challenge. Incorporating new and nontraditional skills into an already complex and challenging clinical curriculum and practice is not easy. This makes development of methods for curricular design, teaching and assessment of anesthesiology resident and fellow performance essential. The Domains of learning, particularly the Affective Domain can serve as an organizing structure for developing objectives and selecting teaching and assessment techniques. Using the Affective Domain to select targeted teaching techniques might help foster development of key beliefs and values that underlie the advanced competencies (and sub-competencies). Targeted teaching, outside of the patient care arena, when combined with traditional clinical teaching practices, may help to ensure continued performance of desired behaviors. These include acting in a consultative role for other health professionals (ICS), providing culturally responsive care (Professionalism), using evidence to enhance the care of patients (PBLI), and advocating for quality of care and working to enhance patient safety (SBP). As educators, our aim is not only to impact knowledge, attitudes and skills, but to impact the daily behavior of our graduates.